Effect of co-presence of cadmium or procymidone with microplastic films in soil on lettuce growth - Eun Hea Jho; Ji Won Yang; Won Jung Ju; Sung-Jong Lee; Md Mehedee Hasan (Applied Biological Chemistry, 2023)
Abstract Agricultural environment is often contaminated with various chemicals (e.g., pesticides, heavy metals) and microplastics due to the uses of plastic products. The effects of chemical contaminants or microplastics on terrestrial environment have been extensively studied, but the studies on the co-presence of chemical contaminants and microplastics are relatively limited. This study was set to investigate the effect of co-presence of microplastics (i.e., low-density polyethylene (LDPE) and polyvinyl chloride (PVC) microplastic films) and chemical contaminants (i.e., cadmium (Cd) and procymidone (PCM)) in soil on the lettuce growth and Cd and PCM uptake by lettuce using pot tests. The lettuce leaf lengths were not affected by the presence of only Cd or PCM, but the rates of change in the lettuce leaf number were adversely affected by the presence of PCM. The presence of only LDPE or PVC in soil at the concentrations used in this study did not have significant impacts on the lettuce growth. But the co-presence of Cd and LDPE and the co-presence of PCM and PVC resulted in the negligible increases in the lettuce leaf length and leaf number with time, although the lettuce growths were statistically similar in the Cd- or PCM-contaminated soils regardless of the presence of microplastics. The results suggest that the adverse effects of Cd or PCM can be intensified by the co-presence of microplastics, and the effects can be different depending on the types of microplastics. The promoted adverse effects of chemical contaminants in the co-presence of microplastics can be supported by the tendency of the increased absorption of Cd or PCM by lettuce in the co-presence of microplastics. Overall, this study shows the need for management of both chemical contaminants and microplastics that may reside in the agricultural environment.